State, Constitution, and Identity of Power: A Socio-Political Analysis of the Debate on the Minimum Age Requirement for Presidential and Vice Presidential Candidates - Samudro, Muhammad Jalu; Enggarani, Nuria Siwi (Universitas Pattimura, 2025)
Indonesia, as a democratic and constitutional state, places the law and the 1945 Constitution (UUD 1945) as the primary foundation of state governance. A key expression of this principle is the Constitutional Court’s authority to review legislation against the Constitution, as stipulated in Article 24C paragraphs (1) and (2). This article critically analyzes Constitutional Court Decision No. 90/PUU-XXI/2023 concerning the minimum age requirement for presidential and vice-presidential candidates from socio-political and constitutional law perspectives. Using a socio-legal research approach, it examines legal documents within the broader context of power, political identity, and constitutional dynamics. The analysis reveals that the Court’s revision of Article 169 letter q of Law No. 7/2017 on Elections—by introducing an alternative requirement for candidates under 40 who have held or currently hold elected office—reflects an expansion of judicial interpretation beyond constitutionally defined authority. Substantively, the ruling raises legitimacy concerns and opens pathways for political interests to influence legal processes. The novelty of this study lies in its interdisciplinary approach that combines legal analysis and power discourse to explain the shifting boundaries of constitutional authority in Indonesia. It recommends clearer limitations on judicial power and stronger political and ethical oversight mechanisms for the Constitutional Court to safeguard democratic integrity.